A Green Integrated Inventory Model for a Three-Tier Supply Chain of an Agricultural Product - Islam, S. M. Shahidul; Hossain, Risat; Yasmin, Mst. Jamila (Engineering International, 2020)
Green supply chain management coordinates environment issues into the supply chain business. It has been popular to both academicians and practitioners. Smooth supply of processed agricultural products is essential for human beings and pets. In some models, excess raw materials, byproducts and defected products are kept neglected in producing and marketing finished products. Here, we have presented a three-tier green supply chain model for an agricultural product where byproducts are used for some purposes. Solution procedure of the model is derived. We have demonstrated the model using two numerical example problems.